SFRT combined with immunotherapy for a growing hepatocellular carcinoma after the failure of anti-angiogenesis and anti-PD1 treatment: a case report - Hu, Jiamiao; Jin, Yue; Wang, Mengjia; Pang, Yuke; Wang, Shenkangle; Xie, Xuyun; Wang, Zhewen; Sun, Xiaonan (Frontiers in Oncology, 2025)
BackgroundHepatocellular carcinoma (HCC) is one of the prevalent tumors worldwide, posing a global healthcare threat. The existing treatment options for large HCC have poor therapeutic effects and are prone to drug resistance. Spatially fractionated radiation therapy (SFRT) is a highly precise radiotherapy technique that delivers a concentrated high dose of radiation to a well-defined tumor target while minimizing radiation exposure to the surrounding normal tissues. SFRT specially delivers a non-uniform radiation dose to the target area instead of a homogeneous dose throughout the tumor volume. This steep dose gradient within the targeted tumor could increase the immune-rich infiltrate within the tumor, thus enhancing the efficacy of immunotherapy.Case reportA 22-year-old man was diagnosed with large HCC, classified as Barcelona Clinic Liver Cancer (BCLC) stage C. The patient received first-line systemic treatment with bevacizumab and atezolizumab, followed by locoregional therapy with hepatic arterial infusion chemotherapy (HAIC). The tumor rapidly grew over the next 2 months. Subsequently, the patient underwent SFRT combined with anti-PD1/CTLA4 (anti-programmed death 1/anti-cytotoxic T-lymphocyte antigen-4) immunotherapy and anti-angiogenesis treatment. SFRT was administered using volumetric modulated arc therapy, delivering 26.68 Gy in two fractions every other day to the high-dose spheres and 8 Gy in two fractions to the targeted tumor. The tumor regressed nearly 40% over 2 months after the treatment, without significant treatment-related side effects (grade 3 or 4 acute and subacute toxicities) observed during the subsequent follow-up exams.ConclusionSFRT combined with immunotherapy is a promising strategy for large HCC.